Chapter 18 Affective Pedagogies, and Pedagogies of Affect - Kouri-Towe, Natalie (Taylor & Francis, 2023)
The study of affect is one of the most exciting and wide-ranging topics to have emerged in the humanities and social sciences in recent years and continues to generate research and debate. It has particularly important implications for the study of gender, as this outstanding handbook amply demonstrates. It is the most comprehensive volume to date, engaging with the intersections between gender and affect studies. A global and interdisciplinary range of contributors articulate the connections (and disconnections) between gender, sexuality, and affect in a range of geographical and historical contexts. Comprising over 40 chapters, the Companion is divided into six parts: Affects of Gender, Affective Relations, Relational Affects, Affective Practices Representing Affects, Geographical and Spatial Affects, Affects of History, Histories of Affect. Topics examined include intersections between gender and affect over topics including queerness, trans*, feminism, masculinity, race/ethnicity, disability, animality, media, posthumanism, technology, sound, labor, neoliberalism, protest, and temporality. This is an outstanding collection that will be invaluable to scholars and students across a range of disciplines, including gender and sexuality studies, cultural studies, literature, media, and sociology.